USE OF PRACTICAL TRAINING AND INDEPENDENT WORK IN TEACHING MATHEMATICS (Academicia Globe: Inderscience Research, 2022)
It is appropriate to take into account that the optimization of the educational process does not require the constant use of any form of education, but the harmony of forms. In the following article, the forms and methods of teaching with the help of practical training and self-study forms of education in the teaching of professional subjects, including: mathematics, are widely covered.